The growth-poverty nexus: Evidence from Kazakhstan - Akram Esanov (Asian Development Bank Institute (ADBI), 2006)
This paper examines the extent, dynamics and distribution of poverty in Kazakhstan during the period of 2001-2004. Furthermore, the study decomposes changes in poverty into growth and redistribution components. The analysis demonstrates that over the period of 2001-2004 both the incidence and the depth of poverty have significantly declined, improving the living standards of population. The decomposition of changes in poverty reveals that the fall in poverty was entirely driven by the improvements in the inequality, whereas the growth appears to be poverty enhancing.
Keywords: 330